ANALISIS KEBIJAKAN PELAYANAN KESEHATAN GRATIS TERHADAP TINGKAT KEPUASAN MASYARAKAT DI DESA BULO WATTANG KECAMATAN PANCA RIJANG - DIAN Ikawati (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2018)
This reaserch aims to know the policy of the free health services at the of Bulo Wattang sub-district Panca Rijang and to know the level of community statisfaction of Bulo Wattang subdistrict Panca Rijang village population research. Is as much as the samples in 427, the disived sample researchersis 10% or 81 communities that receive public health security card , taken on the basis of random sampling techniques. The type of this research is descriptive quantitatif data collection techniques. Done the data is done in this research is to use techniques of observation, questionaire and study at the library. Data collected and then analyzed by using frequency and percentage table. The result of this research to the indicator X shows that free health care policy is 49,15% of produced and bevads on the category less satisfied. While the indicator Y indicates that the level of satisfaction of society is 49,78% fall in to the category of less satisfied. So the result accumulation and on each indicator is 49% are on the category less satisfied.